ShaPINg Cell Fate Upon DNA Damage: Role of Pin1 Isomerase in DNA Damage-Induced Cell Death and Repair - Polonio-Vallon, Tilman; Krüger, Daniel; Hofmann, Thomas G. (Frontiers in Oncology, 2014)
The peptidyl-prolyl cis/trans isomerase Pin1 acts as a molecular timer in proline-directed Ser/Thr kinase signaling and shapes cellular responses based on recognition of phosphorylation marks and implementing conformational changes in its substrates. Accordingly, Pin1 has been linked to numerous phosphorylation-controlled signaling pathways and cellular processes such as cell cycle progression, proliferation and differentiation. In addition, Pin1 plays a pivotal role in DNA damage-triggered cell fate decisions. Whereas moderate DNA damage is balanced by DNA repair, cells confronted with massive genotoxic stress are eliminated by the induction of programmed cell death or cellular senescence. In this review we summarize and discuss the current knowledge on how Pin1 specifies cell fate through regulating key players of the apoptotic and the repair branch of the DNA damage response.